Investigating the relationship of work stress with job motivation: A study on Central Seberang Perai District and Land Office / Nur Izzati Zulkifli - Zulkifli, Nur Izzati (Bachelor of Science (Hons.) Statistics, 2015)
This study examined the structural equation model of role ambiguity, role overload, role conflict, job stress and job motivation with mediating of the job stress. In this paper, the purpose to evaluate the role ambiguity, role conflict and role overload with job motivation. The results from a sample of 129 employees in a PDTSPT organization indicate that: 1. There are significant and direct effect between role ambiguity with job motivation.2.There are not significant between role conflict and overload with job motivation. 3. Job stress has been mediate relationship between role ambiguity and job motivation. 4. Job stress has not been mediate relationship between role conflict and overload with job motivation. 5. There is not significant relationship between job stress and job motivation. That is, when role ambiguity is low, there will be a high level of job motivation in an organization towards their works